Temporal intrailiac balloon occlusion for the treatment of intractable pelvic fracture hemorrhage - Ishida, Kenichiro (Acute Med Surg, 2015)
CASE: A 48‐year‐old schizophrenic man sustained multiple injuries following a fall. Unstable pelvic fractures were diagnosed in the emergency department. The patient's hemodynamic status was stabilized following bilateral internal iliac artery embolization using a gelatin sponge. However, recurrent bleeding and an expanding retroperitoneal hemorrhage occurred 1 h after transcatheter arterial embolization. OUTCOME: Using temporal intrailiac balloon occlusion, with preperitoneal gauze packing, the patient's hemodynamic status was stabilized in the intensive care unit. No complications were observed following transcatheter arterial embolization and balloon occlusion. CONCLUSIONS: Temporary intrailiac balloon occlusion is a rapid and safe treatment for refractory pelvic hemorrhage, which can be administered simultaneously with other treatments including preperitoneal gauze packing and external fixation.